Multiple-batch spawning: a risk spreading strategy disarmed by highly intensive size-selective fishing ... - Hočevar, Sara (Dryad, 2022)
Here we upload the files that support our research on the role of risk-spreading strategies in the light of fisheries-induced evolution. The code is stored in Zenodo. Abstract from the paper: Can the advantage of risk-managing life-history strategies become a disadvantage under human-induced evolution? Organisms have adapted to the variability and the uncertainty of environmental conditions with a vast diversity of life-history strategies. One of such evolved strategies is multiple-batch spawning, a spawning strategy common to long-lived fishes that ‘hedge their bets’, by distributing the risk to their offspring on a temporal and spatial scale. The fitness benefits of this spawning strategy increase with female body size, the very trait that size-selective fishing targets. By applying an empirically and theoretically motivated eco-evolutionary mechanistic model that was parameterized for Atlantic cod (Gadus morhua), we explored how fishing intensity may alter the life-history traits and fitness of fishes ... : We used the empirically-motivated individual-based eco-evolutionary model to simulate the dataset. ...